Acute kidney injury during pregnancy in kidney transplant recipients. Issue 5 (17th April 2022) - Yadav, Anju; Salas, Maria Aurora Posadas; Coscia, Lisa; Basu, Arpita; Rossi, Ana Paula; Sawinski, Deirdre; Shah, Silvi
Abstract: Pregnancy‐related acute kidney injury (AKI) is a public health problem and remains an important cause of maternal and fetal morbidity and mortality. The incidence of pregnancy‐related AKI has increased in developed countries due to increase in maternal age and higher detection rates. Pregnancy in women with kidney transplants is associated with higher adverse outcomes like preeclampsia, preterm births, and allograft dysfunction, but limited data exists on causes and outcomes of pregnancy‐related AKI in the kidney transplant population. Diagnosis of AKI during pregnancy remains challenging in kidney transplant recipients due to lack of diagnostic criteria. Management of pregnancy‐related AKI in the kidney transplant population requires a multidisciplinary team consisting of transplant nephrologists, high‐risk obstetricians, and neonatologists. In this review, we discuss pregnancy‐related AKI in women with kidney transplants, etiologies, pregnancy outcomes, and management strategies.